2021
DOI: 10.1055/s-0041-1722930
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of En Bloc Resection for Advanced Temporal Bone Squamous Cell Carcinoma

Abstract: Objective En bloc and margin-negative surgical resection seems to offer the best prognosis for patients with temporal bone squamous cell carcinoma (TB-SCC). In this study, we summarize the outcomes of surgical cases of advanced TB-SCC (T3–T4) that were managed in two institutions, with an accompanying description of the surgical procedure that was utilized: modified subtotal temporal bone resection (STBR), which involves the en bloc removal of the temporal bone including or transecting the otic capsule. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Conventionally, malignant tumors of the head and neck are treated with en bloc tumor resection to the set safety margins. Zanoletti et al reported that recurrences occurred despite obtaining block resection with negative margin in EAC-SCC [ 15 ], but many previous studies concluded that negative margin resection can improve the prognosis of EAC-SCC [ 16 , 17 , 18 , 19 , 20 , 21 ]. It may be difficult to control positive margin resection with adjuvant therapy [ 22 , 23 , 24 , 25 ], although some studies recommended a piecemeal approach for cases requiring treatment beyond LTBR due to the technical difficulty [ 2 , 3 , 4 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conventionally, malignant tumors of the head and neck are treated with en bloc tumor resection to the set safety margins. Zanoletti et al reported that recurrences occurred despite obtaining block resection with negative margin in EAC-SCC [ 15 ], but many previous studies concluded that negative margin resection can improve the prognosis of EAC-SCC [ 16 , 17 , 18 , 19 , 20 , 21 ]. It may be difficult to control positive margin resection with adjuvant therapy [ 22 , 23 , 24 , 25 ], although some studies recommended a piecemeal approach for cases requiring treatment beyond LTBR due to the technical difficulty [ 2 , 3 , 4 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This method does not require a retromastoid paracondylar approach and, instead, involves a limited posterior mastoidectomy. The limited posterior mastoidectomy enabled us to cut the internal auditory meatus and expose the jugular foramen from the lateral aspect [ 16 ]. However, there is a debate with the mSTBR approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations